Analisis Implementasi Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah (SAK EMKM) Pada Usaha Kecil Menengah UD.Multi Jaya Panglong - Dhea Amelia; Yenni Samri Juliati Nasution; Arnida Wahyuni Lubis (CV. Ulil Albab Corp, 2023)
Indonesia is a developing country with a focus on economic growth through small and large scale businesses that are expected to be sustainable and innovative in their operations. Therefore, the government regulates SAK EMKM to help SMEs manage finances, make economic decisions, and facilitate access to financing from banks or other investors. SAK EMKM is a standard prepared by IAI to fulfill accounting requirements in the financial reports of micro, small and medium entities (EMKM). The Micro, Small and Medium Enterprises (MSME) sector is an important player in the Indonesian economy, providing employment opportunities for many people. Financial reports are the result of the accounting process which can be used as a tool to communicate between financial data or activities of a company and interested parties. This research aims to assess the suitability of small and medium enterprise (SME) financial reports using accounting based on SAK EMKM which is applied to UD. Jaya Multi Enterprise is located at Jl. Bahagia By Pass No.4E, Sudirejo I, Kec. Medan City, Medan City, North Sumatra 20217. This research uses qualitative methods with a descriptive approach, and data is collected through observation, interviews and documentation from UD. Multi Jaya Panglong. Data analysis techniques include data reduction, presentation, and drawing conclusions. The research results show that UD. Multi Jaya Panglong applies accounting practices, but the recording of financial reports is carried out very simply, not in accordance with the provisions in SAK EMKM. Financial reports owned by UD. Multi Jaya Panglong is an income statement. The reason for not implementing SAK EMKM at UD. Multi Jaya Panglong is a lack of knowledge and understanding in preparing business financial reports based on SAK EMKM.